Status of the Waterbirds of Sunabeda Wildlife Sanctuary, Odisha, India - Lahkar, Dipankar; Sahu, H. K.; Rahman, S. (Indian Forester, 2015)
A study was carried out on the population of water birds in two wetlands Raital Bandh and Jalkil Bandh of the Sunabeda Wildlife Sanctuary, Odisha, India, in two successive years 2009 and 2010. 4,701 Individuals of 29 species of birds belonging to 12 families in both years were earmarked. Highest number of waterbirds observed in Raital Bandh in both years. All total eight winter and twenty one resident species identified during the study period. The family Anatidae (46.67% & 51.30%) in Raital Bandh and 60.79% & 58.14% respectively in Jalkil Bandh forms the main bulk of the waterbirds population. Species diversity was found highest in Raital Bandh in 2009 (1.398) and in 2010 Jalkil Bandh (1.342). The depth of the water and siltation was the major problem in winter of these two wetlands. Illegal activities like netting, killing of wild birds are continuously major threats for the conservation.